Investigation of the Effect of Grout Viscosity on The Bearing Capacity of Sandy Soil. - Oriokot, William (Kabale University, 2023)
Grouting is one of the most effective and commonly used soil stabilization technique for weak soils and rock formations. Cement grouts are mainly used in most engineering works since they have low costs and readily available. However, in practice during cement grouting, much emphasis is put on the flowability of the grout and reduction of the grouting time. This leads to further adjustment of the water-cement ratio without observing its effects on the strength attained by the soil. This project aims at investigating the effect of grout viscosity on the bearing capacity of sandy soil and to develop a relationship between the water-cement ratio of the grout and the expected CBR value which will be related with the bearing capacity of soil attained at a certain viscosity. The developed relationship aims at guiding the grouting personnels when adjusting the water-cement ratio of the grout so as not to overrate flowability and underrate the expected bearing capacity. In this project, permeation grouting technique was employed during soil stabilization using cement as a grouting material. Soil tests were conducted, which included; particle size distribution and CBR test while the viscosity test was carried out on the grout using the Marsh funnel viscometer. Results indicate that the penetration resistance of the grouted soil decreases with a decrease in the viscosity of the grout. The grouting times for grouts of different water-cement ratios also increased as the viscosity of the grout increased. An empirical equation that relates the water-cement ratio and the penetration resistance of the soil has been developed. The equation can be used in grouting works to determine the CBR value of soil at a certain W/C of grout, hence relating to the expected bearing capacity of soil.